PERAN PEMIMPIN PEMBELAJAR DALAM PEMBELAJARAN YANG BERKUALITAS - Idris, Ahmad; Syarifudin, Encep; Gunawan, Agus (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT The role of learning leaders is crucial in creating quality education. A learning leader is an individual capable of facilitating, inspiring, and motivating a learning community to continuously grow and innovate. This study aims to analyze the contribution of learning leaders in establishing an effective, inclusive, and relevant learning ecosystem that meets the demands of the 21st century. The approach employed is a literature review, examining the concept of learning leadership, its role in educational management, and its impact on the quality of teaching and learning processes and outcomes. The findings indicate that learning leaders play a pivotal role in fostering a culture of continuous learning, enhancing educators' competencies, and ensuring the implementation of student-centered teaching strategies. By applying transformational leadership, learning leaders can promote innovation, collaboration, and reflection that support the achievement of high-quality education. This study provides recommendations for education leaders to develop their skills as learning leaders. These skills are essential to improve the quality of learning in various educational contexts. With strong leadership abilities, education leaders can create innovative and inclusive learning environments. This is expected to support the continuous improvement of education quality. ABSTRAK Peran pemimpin pembelajar sangat penting dalam menciptakan pembelajaran yang berkualitas. Pemimpin pembelajar adalah individu yang mampu memfasilitasi, menginspirasi, dan memotivasi komunitas belajar untuk terus berkembang dan berinovasi. Penelitian ini bertujuan untuk menganalisis kontribusi pemimpin pembelajar dalam menciptakan ekosistem pembelajaran yang efektif, inklusif, dan relevan dengan kebutuhan abad ke-21. Pendekatan yang digunakan adalah studi literatur dengan menganalisis konsep pemimpin pembelajar pembelajaran, perannya dalam manajemen pendidikan, serta dampaknya terhadap kualitas proses dan hasil pembelajaran. Hasil penelitian menunjukkan bahwa pemimpin pembelajar memiliki peran kunci dalam mengembangkan budaya pembelajaran berkelanjutan, meningkatkan kompetensi tenaga pendidik, serta memastikan penerapan strategi pembelajaran yang berbasis siswa. Dengan menerapkan pemimpin pembelajar transformasional, pemimpin pembelajar mampu mendorong inovasi, kolaborasi, dan refleksi yang mendukung terciptanya pendidikan berkualitas tinggi. Penelitian ini memberikan rekomendasi bagi para pemimpin pendidikan untuk mengembangkan keterampilan sebagai pemimpin pembelajar. Keterampilan tersebut penting untuk meningkatkan kualitas pembelajaran di berbagai konteks pendidikan. Dengan kemampuan kepemimpinan yang baik, pemimpin pendidikan dapat menciptakan lingkungan belajar yang inovatif dan inklusif. Hal ini diharapkan dapat mendukung peningkatan mutu pendidikan secara berkelanjutan.